Fecal Elastase in Preterm Infants to Predict Growth Outcomes. Issue 2 (1st December 2022) - Holzapfel, Lindsay F.; Hair, Amy B.; Preidis, Geoffrey A.; Halder, Tripti; Yang, Heeju; Unger, Jana P.; Freedman, Steven; Martin, Camilia R.
Abstract : Objectives: Preterm infants are born functionally pancreatic insufficient with decreased pancreatic production of lipase and proteases. Developmental pancreatic insufficiency (PI) may contribute to reduced nutrient absorption and growth failure. We sought to determine longitudinal fecal elastase (ELA1) levels in a cohort of preterm infants and whether levels are associated with growth outcomes. Methods: Prospective observational study of 30 infants 24–34 weeks gestational age and birth weight ≤1250 g fed the exclusive human milk diet, consisting of human milk with human milk-based fortifier. ELA1 was quantified by ELISA during the first 2 weeks of life [Early; 7.5 ± 1.8 days of life (DOL)] and after attainment of full, fortified feedings (Late; 63.6 ± 24.1 DOL). Results: Early ELA1 levels were 192.2 ± 96.4 µg/g, and Late ELA1 levels were 268.0 ± 80.3 µg/g, 39.4% higher ( P = 0.01). Infants with early PI (ELA1 < 200 µg/g) were more likely male and of lower gestational age, weight, length, and head circumference at birth. These variables, but not PI status, independently predicted somatic growth. Conclusions: Fecal ELA1 in preterm infants fed exclusive human milk diet increases with postnatal age. Although pancreatic function in preterm infants may serve as a biological contributor to early postnatal growth failure, additional studies using fecal ELA1 as a predictive biomarker for growth failure are needed in larger cohorts.